Optimalisasi Game Learning Kahoot dalam Evaluasi Pembelajaran Daring Matematika di SMKN 1 Singgahan Tuban - Hidayat Rahman (LP. Ma'arif Janggan Magetan, 2021)
Abstract: This descriptive qualitative research offers an evaluation model for Mathematics learning problems that have stagnated due to the rigidity of manual exams and exercises with the Kahoot application. This Kahoot application is equipped with tutorials, pictures, and practical testing tools and their feedback. At least there are some problems in Mathematics learning faced by teachers at SMKN 1 Singgahan Tuban, namely, difficulties in utilizing technological devices, 2) there are limitations in making learning evaluation questions with virtual applications. 3) learning evaluation is still carried out in a monotone. The Kahoot application is an appropriate evaluation model to answer three mathematics learning problems. That is because Kahoot has a small difficulty level, making it easy to practice. Apart from being virtual based and having direct feedback, the Kahoot evaluation model can save all test results into Google Drive. Kahoot application, teachers/educators can offer some questions to answer. Students are more interactive and happy. Moreover, this application is equipped with a rating system as feedback. Abstrak: Penelitian kualitatif deskriptif ini menawarkan model evaluasi atas problem pembelajaran Matematika yang mengalami stagnasi akibat kekakuan dari ujian dan latihan yang bersifat manual dengan aplikasi Kahoot. Aplikasi Kahoot ini dilengkapi dengan tutorial, gambar dan perangkat alat uji praksis beserta umpan baliknya. Setidaknya ada beberapa problematika pembelajaran Matematika yang dihadapi guru terjadi di SMKN 1 Singgahan Tuban yakni, kesulitan dalam memanfaatkan perangkat teknologi, 2) adanya keterbatasan dalam membuat soal evaluasi pembelajaran dengan aplikasi virtual. 3) evaluasi pembelajaran masih dilakukan dengan monoton. Aplikasi Kahoot adalah model evaluasi tepat untuk menjawab tiga problem pembelajaran Matematika. Hal ini karena Kahoot memiliki tingkat kesulitan yang kecil, sehingga mudah untuk dipraktikan. Selain juga berbasis virtual dan terdapat umpan balik (feedback) langsung, model evaluasi Kahoot dapat menyimpan segala hasil tes ke dalam Google Drive. Aplikasi Kahoot, guru/pendidik dapat menyodorkan beberapa soal untuk dijawab. Peserta didik lebih interaktif dan senang, apalagi aplikasi ini dilengkapi dengan sistem peringkat sebagai umpan balik. DOI: https://doi.org/10.33399/edukasia.v2i1.39